2017
DOI: 10.1371/journal.pone.0184914
|View full text |Cite
|
Sign up to set email alerts
|

The association between cigarette smoking and inflammation: The Genetic Epidemiology Network of Arteriopathy (GENOA) study

Abstract: To inform the study and regulation of emerging tobacco products, we sought to identify sensitive biomarkers of tobacco-induced subclinical cardiovascular damage by testing the cross-sectional associations of smoking with 17 biomarkers of inflammation in 2,702 GENOA study participants belonging to sibships ascertained on the basis of hypertension. Cigarette smoking was assessed by status, intensity (number of cigarettes per day), burden (pack-years of smoking), and time since quitting. We modeled biomarkers as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 45 publications
3
54
3
1
Order By: Relevance
“…Prevalence of cigarette smoking in the general population has been recently reported to be around 15% (data from the US) ( 49 ); this prevalence appears to be increased in patients with axSpA, with reported numbers up to 30 and 40% ( 5 , 50 ). Furthermore, smoking has been associated with increased acute phase reactants [high sensitivity CRP ( 51 )], but also, in the specific case of axSpA, with increased disease activity and structural progression ( 52 54 ); therefore, smoking in axSpA patients would have a double role, as traditional CVRF but also increasing disability and ankylosis, which might potentially lead to a more sedentary lifestyle, another very well-known traditional CVRF.…”
Section: Cardiovascular Diseasementioning
confidence: 99%
“…Prevalence of cigarette smoking in the general population has been recently reported to be around 15% (data from the US) ( 49 ); this prevalence appears to be increased in patients with axSpA, with reported numbers up to 30 and 40% ( 5 , 50 ). Furthermore, smoking has been associated with increased acute phase reactants [high sensitivity CRP ( 51 )], but also, in the specific case of axSpA, with increased disease activity and structural progression ( 52 54 ); therefore, smoking in axSpA patients would have a double role, as traditional CVRF but also increasing disability and ankylosis, which might potentially lead to a more sedentary lifestyle, another very well-known traditional CVRF.…”
Section: Cardiovascular Diseasementioning
confidence: 99%
“…In the study of Xia et al (25), which reported an association with CRP and CSF, the rate of smoking of the CSF group was higher than the control group. It is well defined in the literature that cigarette smoking significantly increases systemic inflammation and serum CRP values (29,30). In our study, the similarity of age, BMI, systolic blood pressure, diabetes, and hyperlipidemia rates between the two groups made the result of our study more valuable by limiting the possible confounding factors.…”
Section: Discussionmentioning
confidence: 59%
“…Accordingly, IL-6 levels in male smokers are twice the levels in non-smokers. Some studies reported that levels of inflammatory cytokines, such as TNF-α and CRP, are higher in smokers than non-smokers (20,21). Acute and response measuring of IL-6 as important pro-inflammatory cytokines to exercise test in cigarette smokers was the strength of the present study.…”
Section: Discussionmentioning
confidence: 67%